Classic I '87 : Biennale waar classique nouveau en classique niveau elkaar ontmoeten. - Classic I 87, Kortrijk; Asselman, Marcel; Bartholomeus, Raymond; Bossu, Joseph; Dhaenens, Lieven; Drugmant, F.; Ellegiers, Daniël; Feys, Bebert; Gerard, Rik; Ghadimi; Heesters, J.H.P.; Hervy, J.J.; et al. (Kortrijk: Classic, 1987)
Aalto, Alvar ; Brendel, Erich ; Breuer, Marcel ; De Bruyne, Pieter ; Dierickx, Karel ; Eysselinck, Gaston ; Gaudi, Antonio ; Gentils, Frans ; Gray, Eileen ; Gropius, Walter ; Hoffman, Jozef ; Keler, Peter ; Kuramata, Shiro ; Le Corbusier ; Mackintosh, Charles Rennie ; Madlener, Jörg ; Mies van der Rohe, Ludwig ; Peire, Luc ; Plensa, Jaume ; Pomodoro, Arnaldo ; Prouvé, Jean ; Rasero, Miguel ; Rietveld, Gerrit Thomas ; Saarinen, Eliel ; Terragni, Giuseppe ; Veranneman, Emiel ; Vermeersch, José ; Wright, Frank Lloyd
Classic I '87 : Biennale waar classique nouveau en classique niveau elkaar ontmoeten, november 1987
Nederlands & Frans & Engels
boek